Proposed Drilling into Postglacial Faults : The Pärvie Fault System - Ask, Maria; Kukkonen, Ilmo; Olesen, Odleiv; Lund, Björn; Fagereng, ÅKe; Rutqvist, Jonny; Rosberg, Jan Erik; Lorenz, Henning (Cambridge University Press, 2021)
The existence of postglacial faults (PGFs) in northern Fennoscandia was first documented in Finland in the last century. Subsequently, over a dozen large PGFs have been observed in Finland, Sweden and Norway. PGFs have been investigated through geophysical methods, trenching and mapping of brittle deformation structures. No direct measurements of the age of faulting exist, although relative ages with respect to glacial (sedimentary) deposits have been established. Very little is known about PGFs through direct measurements. A few short – up to 500 m deep – boreholes exist. Plans for a scientific drilling program were initiated in 2010, but data coverage was relatively unevenly distributed and no PGF was identified as a drilling target. Subsequently, additional data have been collected, and the drilling target has been identified; the Pärvie Fault System is the longest known PGF in the world and has been proposed to have hosted an M8 earthquake near the end or just after the last glaciation. Further, this fault system is still microseismically active. Drill sites are north of the Arctic Circle, in a sparsely populated area. Existing site survey data, established logistics and societal relevance viz the fault’s proximity to mining and energy operations make this fault system an appropriate target. The International Continental Scientific Drilling Program (ICDP) approved a full drilling proposal in October 2019. This chapter presents an abbreviated version of the approved proposal.